Korelasi Konflik, Stres, Budaya Organisasi dan Motivasi Terhadap Kinerja Karyawan BPR Nur Semesta Indah Di Kabupaten Jember - Fauzan Muttaqien; Retno Cahyaningati (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2023)
This study aims to determine the effect of conflict, stress, organizational culture and motivation on employee performance partially or simultaneously. The research method used is quantitative with multiple linear regression analysis techniques. The sampling technique uses a saturated sample with a total sample of 42 respondents. The research was conducted by distributing questionnaires to BPR Nur Semesta Indah Kencong Jember employees. The results of this study indicate that conflict and organizational culture partially have a positive effect on employee performance. While stress and motivation have no effect on employee performance. However, conflict, stress, organizational culture and motivation simultaneously influence employee performance. The results of the study show that conflict, stress, organizational culture and motivation affect employee performance with a determination coefficient of 91.8%, while the remaining 8.2% employee performance is influenced by other variables outside of this study. These results indicate that conflict, stress, organizational culture and motivation are important factors that can improve the performance of BPR Nur Semesta Indah employees. From the research results, it is suggested that PT. BPR Nur Semesta Indah can improve, maintain and improve relations between employees. Other researchers are expected to be able to add independent variables in further research, such as work environment and style of leadership.